Implementasi Push Notification Pada Sistem Penjadwalan Shift Kerja Dengan Metode Firebase Cloud Messaging Berbasis Website (Studi Kasus : RS Sari Asih Sanghiang) - Erpan Kurniawan; Bagas Setiyaki Wicaksono (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Sari Asih Sanghiang Hospital is a company engaged in the health sector. This hospital has been operating since 1994 as a mother and child hospital which was later upgraded to a general hospital in 2009. Based on current observations and observations, the scheduling system for employees working in the hospital has not implemented a computerized system, the current scheduling system input using Microsoft Excel by the head of the room, and distributed to employees in the form of paper through the hospital information board, then taking pictures to be shared with WhatsApp groups, so that each employee can download and view their respective work schedules. Where the system often causes several technical problems, such as loss of schedule data due to the deletion of files from mobile phones or groups, as well as ineffective file management. In overcoming these problems, the author conducted research to create a web-based work shift scheduling system with push notifications to help the head of the Sari Asih Sanghiang Hospital in scheduling each employee's work shift more quickly and easily. In this writing, the author uses a programming language, namely PHP and Visual Studio as a text editor, as well as a MySQL database as data storage and the Waterfall Model as a design flow. It is hoped that this work shift scheduling can simplify the scheduling process and deliver real time information that can assist the Head of the Room in processing Scheduling data, and can provide information to employees so that the information conveyed is more effective.